1994
DOI: 10.1016/0014-5793(94)80202-5
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D activity of isolated rat brain plasma membranes

Abstract: With ["'Cloleate-1abeled phosphatidylcholine as a substrate for phospholipase D the hydrolytic activity was measured by phosphatidic acid formation and the transphosphatidylation activity was measured by the phosphatidylethanol formed in the presence of ethanol. The pH optimum was 6.5 with dimethylglutarate as the buffer. EGTA inhibited the transphosphatidylation activity to a greater extent than the hydrolytic activity. In contrast CaCl,, BaCI,, MgC& and SrCI, stimulated the hydrolytic activity without effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Traces of PLD activity were detected in cytosol prepared from brain (Chalifour and Kanfer, 1980;DeVries et al, 1983;Hattori and Kanfer, 1985;Song et al, 1993;Exton, 1994) and other tissue (Exton, 1994). Isolated rat brain plasma membranes possess PLD activity (Kanfer and McCartney, 1994), which may be the form of this enzyme responding to receptor occupancy. The properties of the PLD activity were documented for human polymorphonuclear leukocytes (Exton.…”
mentioning
confidence: 95%
“…Traces of PLD activity were detected in cytosol prepared from brain (Chalifour and Kanfer, 1980;DeVries et al, 1983;Hattori and Kanfer, 1985;Song et al, 1993;Exton, 1994) and other tissue (Exton, 1994). Isolated rat brain plasma membranes possess PLD activity (Kanfer and McCartney, 1994), which may be the form of this enzyme responding to receptor occupancy. The properties of the PLD activity were documented for human polymorphonuclear leukocytes (Exton.…”
mentioning
confidence: 95%
“…For example, activation of L-serine base enzyme (Kanfer & McCartney, 1991), phospholipases D (Kiss & Anderson, 1990;Lavie & Liscovitch, 1990) and C (Hashizume et al, 1992), and inhibition of phosphatidate phosphohydrolase (Lavie et al, 1990;Mullman et al, 1991) by sphingosine lead to increased synthesis of acidic phospholipids. Increased phosphatidic acid levels have been shown to accompany sphingosine-stimulated proliferation of quiescent Swiss 3T3 cells (Zhang et al, 1990b), and a PKC-independent modulatory role for sphingosine on cell growth was suggested (Zhang et al, 1990a).…”
mentioning
confidence: 97%
“…Exposure to oxygen-derived free radicals also stimulates cellular PLD activity (8,9). Using PLD from various sources, it has been shown that divalent metal ions can activate this enzyme (10,11).…”
mentioning
confidence: 99%